Copyright Of Communal Cultural E Copyright Of Communal Cultural Expressions From An Indonesian Legal Perspective: An Analysis Of Supreme Court Decision No. 591 K/Pdt.Sus-Hki/2024 - Anik Tri Haryani; Retno Catur Kusuma Dewi (Sahaja: Journal Sharia and Humanities, 2026)
Supreme Court Decision No. 591 K/Pdt.Sus-HKI/2024 marks a significant milestone in the legal protection of communal cultural expressions (EBK) in Indonesia. This case involved the copyright registration of the Human Personal Symbol by an individual, which was deemed unlawful because the symbol is part of the Sapta Darma religious teachings and constitutes collective cultural heritage. The Court ruled that the symbol cannot be claimed as an exclusive personal right, as it lacks the element of personal originality and possesses spiritual significance. This study employs a normative legal methodology with a legislative and case law analysis approach to examine the extent to which positive law protects CCE from individual claims. The research findings indicate that Law No. 28 of 2014 on Copyright explicitly protects traditional cultural expressions as state property and cannot be transferred to individuals. This ruling has significant implications for the development of a communal intellectual property registration system, the protection of collective moral rights, and the importance of indigenous communities’ involvement in legal processes. In conclusion, the state needs to strengthen a legal system that prioritizes cultural justice and the protection of communal rights so that the nation’s cultural heritage is not eroded by individual interests.